Physico-chemical and electrical properties of Cryosols in the Lena River Delta - Polyakov, Vyacheslav I. (Вестник Томского государственного университета. Биология)
Vertical electrical sounding method is an express and most accurate method for measuring and analysing the resistivity through the soil profile. As a result of climate change, permafrost is melting, which leads to a significant transformation of landscapes, both natural and anthropogenically transformed. In the vulnerable environments of the Arctic region (long recovery after anthropogenic impact), this method allows to determine the active layer thickness and the heterogeneity in the soil structure without disturbing of the soil cover. This method is based on the measurement of electrical resistivity in the soil, the data obtained were processed in the form of one dimensional model. In the course of field research, the heterogeneous islands of the Lena River Delta were investigated. Complex soil investigations using the method of vertical electrical sensing allows to fully assess the most important properties of cryogenic soils formed in the delta complex of the Lena River. As a result of the work, the modeled boundaries of the active layer were determined, which were confirmed during the laying of soil transects, as well as the main physical and chemical parameters of soils. During the vertical electrical sounding observation an inhomogeneity in the distribution of resistivity under a drained lake was found, which may correspond to the presence of a talik or a layer of salt unfrozen water in a permafrost. Due to the change in the soil horizons, there is a sharp change in the electrical resistivity indicator occur, which corresponds to the change from soil to frozen rock.